(untitled) (Swiss Medical Weekly, 2015)
PRINCIPLES: Employment after kidney transplantation is an important marker of health recovery. The study addresses the impact of successful kidney transplantation on socioeconomic factors and employment in a Swiss cohort. METHODS: Patients who received a kidney allograft at the University Hospital of Basel between 2000 and 2011 were investigated. A standardised survey was used to obtain information on socioeconomic factors 1 year before and after successful transplantation. RESULTS: A total of 610 patients were contacted; 354 (58%) answered the survey. The median age of respondents was 53.5 (interquartile range 42‒61) years at the time of transplantation, 31.2% were females. Overall, 201 out of 282 working-age patients (71.3%) were working 1 year after transplantation: 102 full-time, 55 part-time, 30 patients part-time with additional disability pension, and 14 housework. Seventy-two patients (25.3%) did not work 1 year after transplantation: 63 patients had a full or partial disability pension, and nine patients were unemployed. Thirty out of 282 working-age patients (10.6%) had improved working ability after transplantation. Employment after transplantation was favoured by: living donor transplantation (p <0.0001), pre-emptive transplantation (p <0.0001), dialysis duration ≤1 year (p <0.0001), preserved employment before transplantation (p <0.0001), and higher education (p = 0.003), whereas age above 50 years (p = 0.006), and dialysis duration > 1 year (p <0.0001) had a negative impact. CONCLUSION: The employment rate in this Swiss cohort before and after successful kidney transplantation is high compared with the literature. A high number of living donors, of pre-emptive transplantations, and short dialysis vintages contribute to this observation.